The relationship between leverage and company value: an approach using industry effect resolution - Mustafa, Yusufi Arif; Haikal, Fahri; Apandi, Aden (Jurnal Riset Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of leverage on firm value by incorporating industry effect resolution. The sample consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using panel data regression with fixed-effects and random-effects models, the research compares the impact of leverage on firm value before and after accounting for industry-specific characteristics. The results indicate that leverage has a positive impact on firm value, both before and after controlling for the industry effect.